Checklists in Femur Fractures: High Adherence After Implementation of Computer-based Pediatric Femur Guidelines. (9th August 2021) - Geiger, Kyle; Orr, Oliver; Gupta, Andrew; Bompadre, Viviana; Goldberg, Michael; Sousa, Ted
Abstract : Introduction: The American Academy of Orthopaedic Surgeons (AAOS) created an evidence-based clinical practice guideline for the care of pediatric diaphyseal femur fractures in 2010. Our institution implemented checklists based off these guidelines embedded in a standardized EMR order. The purpose of this study was to describe compliance with checklist completion and to assess safety improvement in a large urban pediatric hospital. Methods: Retrospective and prospective data were collected from 2 years before and 5 years after checklist implementation. This included the patient safety checklists from August 2011 through August 2016. Patients aged 0 to 18 years with a diaphyseal femur fracture were queried from the EMR and included in this study. Patient charts were reviewed for complications, including nerve injury, pressure sore, leg length discrepancy, loss of reduction, failure of fixation, nonunion, delayed union, and infection. Compliance rates were reported based on the AAOS clinical practice guidelines. Results: A total of 313 patients for the postchecklist period were reviewed in this study. Of 219 patients eligible for inclusion, 198 had checklists completed (group B). This group was compared with 100 patients with diaphyseal femur fractures from the period before implementation of the checklist (group A). We found no statistical difference in the number of patients with complications between groups (12% in both groups, P = 0.988). Postoperative checklists demonstrated that 89.9% of patients (178/198) received age-appropriate treatment consistent with the AAOS guideline recommendations after implementation of the checklist. Before the checklist implementation (group A), 94% (94/100) adhered to the guidelines. Conclusion: This study reveals high compliance rates with the AAOS evidence-based clinical practice guideline for the management of pediatric femur fractures. Implementing standardized checklists is possible by embedding them into the EMR. Implementation of checklists did not improve compliance or patient outcomes.